The Role of Magnesium in Blood Coagulation - Szelényi, I; Rigô, J; Ahmed, B. O; Sos, J (Thrombosis and Haemostasis, 1967)
Hypercoagulative tendencies elicited by saturated fat could be repressed by oral or venous administration of magnesium in acute as well as in long term experiments.Magnesium appears to have double functional importance in coagulation : On the one hand, it exerts direct influence by antagonizing calcium, promoting fibrinolysis, and stabilizing fibrinogen and blood platelets and, on the other hand, it acts indirectly as well in that it causes vasodilatation and favours cellular oxidation.In the dynamic equilibrum of the processes taking part in blood coagulation magnesium appears to play its role as a physiological type of anticoagulant.